A preliminary study of the Mute Swan, Cygnus olor - Perrins, C M; Reynolds, C M (Wildfowl, 1967)
Results of a preliminary study of the Mute Swan in the Oxford area 1960 66. Distribution and movements are discussed: relatively few birds seem to travel any distance during their life and those that do are mostly immature. Mean clutch-size is about six, close to the national average; mortality is about 50% between hatching and fledging in September, and brood-size in September is about three for those pairs with young or two if the unsuccessful breeders are included. About one-third of the remaining young die within nine months October-June. Thereafter mortality is about 3325% per annum for the next two-three years, dropping to 18% for breeding adults (birds most commonly start breeding at three or four). Highest losses appear to occur in late winter and early spring. Life-table data suggest that the Mute Swan is maintaining its numbers within the study area, but there is evidence that there are more suitable nesting sites than there are pairs to occupy them.